Study the effect of some plants extracts on growth of Mycobacterium tuberculosis in Comparison with Ethambutol - Abbas, Maysoon Sabah (The Iraqi Journal of Veterinary Medicine, 2011)
This study was conducted to investigate the inhibition role of alcoholicextracts of plants Trigonella foenumgraecum , Piper cubeba , Piper nigrum,Camphora , Commiphora molmol, Apium graveolens , Arachis hypogaea ,Linum usitatissumun , Cuminum cyminum , Pimpinella anisum , Lepidiumsativum , alcoholic extracts of plants used was prepared and used ofconcentration 200 mg/ml and add 0.2 ml of each extracts to 10 ml of media and0.2 ml of Ethambutol to 10 ml of media the drug for mycobacteria and mediawith out any adding for controls. Cultural media were inoculated with 3 dropsof bacterial suspension ( 1mg /ml ) in concentration 108 cfu/ml from patientsuffering from tuberculosis and after incubation on 37 °C the result readweekly up to 4 weeks . the results showed good growth on the control slopes ,which was evident within 2-3 weeks and no growth on the cultural mediacontain (Arachis hypogea , Cuminum cyminum , Commiphora molmol,Trigonella foenumgraecum , Lepidium sativum , Ethambutol ) it while themedia contain (Piper nigrum , Pimpinella anisum showed than 5 colonies thegrowth inhibition was recorded that means sensitivity of mycobacteria to theextracts mention above, while media contain (Piper cubeba , Camphora , Apiumgraveolens ). showed growth more than 5 colonies and media contain Linumusitatissumun showed good growth which means resistant of mycobacteria tothe extract mentioned above .